Deciphering the Role of Emx1 in Neurogenesis: A Neuroproteomics Approach - Kobeissy, Firas H.; Hansen, Katharina; Neumann, Melanie; Fu, Shuping; Jin, Kulin; Liu, Jialing (Frontiers in Molecular Neuroscience, 2016)
Emx1 has long been implicated in embryonic brain development. Previously we found that mice null of Emx1 gene had smaller dentate gyri and reduced neurogenesis, although the molecular mechanisms underlying this defect was not well understood. To decipher the role of Emx1 gene in neural regeneration and the timing of its involvement, we determine the frequency of neural stem cells (NSCs) in embryonic and adult forebrains of Emx1 wild type (WT) and knock out (KO) mice in the neurosphere assay. Emx1 gene deletion reduced the frequency and self-renewal capacity of neural stem cells (NSCs) of the embryonic brain but did not affect neuronal or glial differentiation. Emx1 KO NSCs also exhibited a reduced migratory capacity in response to serum or vascular endothelial growth factor (VEGF) in the Boyden chamber migration assay compared to their WT counterparts. A thorough comparison between NSC lysates from Emx1 WT and KO mice utilizing 2D-PAGE coupled with tandem mass spectrometry revealed 38 proteins differentially expressed between genotypes, including the F-actin depolymerization factor Cofilin. A global systems biology and cluster analysis identified several potential mechanisms and cellular pathways implicated in altered neurogenesis, all involving Cofilin1. Protein interaction network maps with functional enrichment analysis further indicated that the differentially expressed proteins participated in neural-specific functions including brain development, axonal guidance, synaptic transmission, neurogenesis and hippocampal morphology, with VEGF as the upstream regulator intertwined with Cofilin1 and Emx1. Functional validation analysis indicated that apart from the overall reduced level of phosphorylated Cofilin1 (p-Cofilin1) in the Emx1 KO NSCs compared to WT NSCs as demonstrated in the western blot analysis, VEGF was able to induce more Cofilin1 phosphorylation and FLK expression only in the latter. Our results suggest that a defect in Cofilin1 phosphorylation induced by VEGF or other growth factors might contribute to the reduced neurogenesis in the Emx1 null mice during brain development.